Lexical Polysemy: Lexicographic Implications - García Pérez, Rafael (Linguistik Online, 2010)
This paper intends to show the importance of having linguistic instruments, principally semantic ones, for determining the meaning of words with the greatest precision and, consequently, managing to meticulously establish the different meanings of a dictionary's entry words. As an example, a new definition of the Spanish verb mezclar ('to mix') will be proposed.